TANGGAP SALINITAS TERHADAP PERTUMBUHAN BIBIT AKAR WANGI (Vetiveria zizanioides L.) - Aisar Novita; Hilda Julia; Nini Rahmawati (Politeknik Pembangunan Pertanian Medan, 2019)
Salinity can quickly impede root growth, allowing for absorption capacity and essential mineral nutrients from the soil. The research was conducted at the greenhouse faculty of agriculture University of North Sumatra. The study uses a complete random nonfactorial design which is a conformity of salinity consisting of three factors, an EC salinity level of 0 (water distillation). The parameters observed in this study were plant height, dry weight, and specific leaf width. The salinity treatment shows a tangible effect lowering on growths such as plant height, dried leaf weight, and specific leaf area. The salinity causes cellular turgor to decrease and pressure levels from roots and shoots, this suggests that environmental salinity acts primarily on water absorption.